Revisiting Acetonitrile as Tracer of Biomass Burning in Anthropogenic‐Influenced Environments. Issue 11 (1st June 2021) - Huangfu, Yibo; Yuan, Bin; Wang, Sihang; Wu, Caihong; He, Xianjun; Qi, Jipeng; de Gouw, Joost; Warneke, Carsten; Gilman, Jessica B.; Wisthaler, Armin; Karl, Thomas; Graus, Martin; et al.
Abstract: Acetonitrile (CH3 CN) has been widely employed as biomass burning tracer. However, the current application of CH3 CN absolute mixing ratio as the thresholds may misidentify biomass burning due to the interference from other CH3 CN sources in anthropogenic‐influenced environments. High levels of CH3 CN were observed with minor biomass burning impact but still followed a similar correlation with carbon monoxide (CO), suggesting their shared source, most likely, vehicular emission. By analyzing the available literature including more than 30 worldwide field measurements, the enhancement ratios (EnRs) of CH3 CN to CO for biomass burning were found as 2.01 ± 0.16 ppbv/ppmv, well distinguished from the EnRs obtained in urban measurement (0.26 ± 0.04 ppbv/ppmv). An example is given and the application of EnR to identify biomass burning is discussed. The results suggest that the correlation between CH3 CN and CO and their EnRs can be used as more specific indicators for biomass burning. Plain Language Summary: Biomass burning can contribute significantly to local and regional pollutions. A proper tracer can help us track and quantify biomass burning emissions. In the past few decades, the acetonitrile (CH3 CN) level has been applied as a preferred tracer but the existence of CH3 CN sources other than biomass burning may lead to an overestimation of the burning emissions. Here in this paper, by analyzing our field campaign data and the information from the previous publication, the correlation between acetonitrile and carbon monoxide and their enhancement ratios are found to be more specific indicators for biomass burning without interference from other significant sources. The results would be helpful to reevaluate the biomass burning impact and increase the accuracy of air quality forecasting in future research. Key Points: Several ppbv of CH3 CN can be measured in anthropogenic‐influenced environments with minor biomass burning impact Good correlation between high CH3 CN and CO were revealed showing their shared sources in anthropogenic‐influenced environments Biomass burning can be distinguished from other CH3 CN sources using the enhancement ratios of CH3 CN and CO